Axion portal to scalar Dark Matter: unveiling stabilizing symmetry footprints - Francesco D’Eramo; Tommaso Sassi (Journal of High Energy Physics)
Abstract We investigate the role of an axion-like particle (ALP) as a portal between the dark and visible sectors. Unlike conventional studies, which typically assume fermionic dark matter (DM), we explore the phenomenological implications of scalar DM within this ALP portal framework. A key challenge arises from the fact that the interaction between the ALP spacetime derivative and the spin-one current of the scalar DM can be a redundant operator, which may be removed via a field redefinition. However, this interaction reveals a profound connection to the underlying global symmetry that stabilizes the DM particle. We choose a non-Abelian discrete symmetry, ensuring the persistence of the DM-ALP interactions, and in doing so, unveil a rich phenomenology. Working within a general effective field theory approach, we identify the following hallmark features of our scenario: (i) a relic density determined by semi-annihilations, with an abundance independent of ALP couplings to the visible sector; (ii) direct detection rates naturally suppressed; (iii) indirect detection spectra enriched relative to pure annihilation scenarios, with rates also independent of ALP couplings to visible particles. Lastly, we discuss potential microscopic origins for this framework and highlight the broader implications of our results.